Reciprocal regulation of TWIST1 and OGT determines the decitabine efficacy in MDS/AML - Li, Hongjiao; Wang, Yi; Feng, Shuang; Chang, Kaijing; Yu, Xinwen; Yang, Fenfang; Huang, Haozhe; Wang, Yuanbo; Li, Xiang; Guan, Feng (Cell communication and signaling, 2023)
Chemoresistance poses a significant impediment to effective treatment strategies for myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML). Our previous study unveiled that oncogene TWIST1 interacted with DNA methyltransferase 3a (DNMT3a) to regulate the decitabine (DAC) resistance in MDS/AML. However, the underlying mechanism of TWIST1 dysregulation in DAC resistance remained enigmatic. Here, we found that O-GlcNAc modification was upregulated in CD34 + cells from MDS/AML patients who do not respond to DAC treatment. Functional study revealed that O-GlcNAcylation could stabilize TWIST1 by impeding its interaction with ubiquitin E3 ligase CBLC. In addition, as one typical transcription factor, TWIST1 could bind to the promoter of O-GlcNAc transferase (OGT) gene and activate its transcription. Collectively, we highlighted the crucial role of the O-GlcNAcylated TWIST1 in the chemoresistance capacity of MDS/AML clonal cells, which may pave the way for the development of a new therapeutic strategy targeting O-GlcNAcylated proteins and reducing the ratio of MDS/AML relapse.